Core cracking and hydrothermal circulation can profoundly affect Ceres' geophysical evolution. Issue 2 (6th February 2015) - Neveu, Marc; Desch, Steven J.; Castillo‐Rogez, Julie C.
Abstract: Observations and models of Ceres suggest that its evolution was shaped by interactions between liquid water and silicate rock. Hydrothermal processes in a heated core require both fractured rock and liquid. Using a new core cracking model coupled to a thermal evolution code, we find volumes of fractured rock always large enough for significant interaction to occur. Therefore, liquid persistence is key. It is favored by antifreezes such as ammonia, by silicate dehydration which releases liquid, and by hydrothermal circulation itself, which enhances heat transport into the hydrosphere. The effect of heating from silicate hydration seems minor. Hydrothermal circulation can profoundly affect Ceres' evolution: it prevents core dehydration via "temperature resets, " core cooling events lasting ∼50 Myr during which Ceres' interior temperature profile becomes very shallow and its hydrosphere is largely liquid. Whether Ceres has experienced such extensive hydrothermalism may be determined through examination of its present‐day structure. A large, fully hydrated core (radius 420 km) would suggest that extensive hydrothermal circulation prevented core dehydration. A small, dry core (radius 350 km) suggests early dehydration from short‐lived radionuclides, with shallow hydrothermalism at best. Intermediate structures with a partially dehydrated core seem ambiguous, compatible both with late partial dehydration without hydrothermal circulation, and with early dehydration with extensive hydrothermal circulation. Thus, gravity measurements by the Dawn orbiter, whose arrival at Ceres is imminent, could help discriminate between scenarios for Ceres' evolution. Key Points: New core cracking model coupled to a thermal evolution code Enough fractured rock on Ceres for hydrothermal interaction Hydrothermal circulation can profoundly affect Ceres' evolution